Determinants of Burnout Syndrome in emergency nurses: Integrative Review (Research, Society and Development, 2021)
Currently, Burnout Syndrome has been widely discussed in the literature, since it has a direct and negative impact on the nursing care provided to patients, and on the workers' quality of life, resulting in work incapacity, absenteeism, and other harm. Considering the syndrome as an important public health problem, this study aimed to explore the determinants of Burnout Syndrome in nurses who work in the hospital emergency department. This is an integrative review, which systematized data from the following databases: Scielo, Pubmed, Medline, BDEenf and LILACS. Through the searches, 165 manuscripts were found. After applying the inclusion and exclusion criteria and reading the titles, abstracts and objectives, 12 articles were characterized and summarized for a descriptive approach, which elucidated that gender, overcrowding, violence at work, age, length of service, time hours and low pay were risk factors for BS in emergency nurses. In view of the above, there is heterogeneity regarding the determinants of Burnout among nurses. Considering that nursing is one of the professions susceptible to the syndrome, it is important that managers identify, disseminate and develop strategies that in the medium and long term reduce the rates of Burnout Syndrome. Such practice will contribute to a better quality of life in daily life and during work activities, also resulting in better care provided to patients.